Determinants Of Knowledge-Based Support Systems In It Companies In Yemen - Salem Al-Jifri, Mohammad Abdulla (2008)
The main objectives of this study are to identify the determinants of success of implementing KBSS, and to identify which variables of the internal and external factors can be used to predict and explain success of KBSS.